(untitled) (Coffee Science - ISSN 1984-3909)
The two most commercialized coffee species worldwide are: Coffea arabica L. (arabica) and Coffea canephora Pierre ex A. Froehner (robusta). Since these coffees differ in their commercial value and acceptability, adulteration and mislabeling are major concerns. The diterpenes kahweol and cafestol are considered potential indicators of conilon coffee addition, as they are present in different contents in the species. The degree of roasting and the presence of defective beans may affect the theor of several coffee constituents. The aim of this work was to evaluate the possibility of discriminating the coffee species arabica and robusta through their kahweol and cafestol contents. Samples of arabica, robusta, and of their blends, with different amounts of defects and degrees of roasting (light, medium and dark) were studied. After direct saponification and extraction with terc-butyl methyl ether, the samples were analyzed by reverse-phase HPLC with UV detection. The kahweol content varied between 661 and 923 mg/100 g in the arabica coffee, and its presence was not observed in the conilon. Cafestol ranged from 360 to 478 mg in arabica, and from 163 to 275 mg/100 g in conilon coffee. The addition of conilon coffee reduced diterpene contents, but this effect varied according to the amount of defects and roasting degrees. A higher intensity roast did not affect diterpene degradation. No differences in the kahweol and cafestol levels, comparing defective or regular beans, were observed. In the analysis of coffee samples with different degrees of roasting and defects, the parameters kahweol and cafestol showed potential for discriminating between the species.